Tantangan Implementasi Yurisdiksi ICC dalam Penegakan Hukum atas Kejahatan Genosida di Negara Non-Pihak - Anisah, Aura; Wahdah, Azzhara Nikita; Nirwana, Rena Putri; Arini, Dita Rosalia (Media Hukum Indonesia (MHI), 2025)
The International Criminal Court (ICC) is a permanent judicial institution established under the 1998 Rome Statute, with a mandate to try serious crimes such as genocide, crimes against humanity, and war crimes. Although ICC jurisdiction formally applies to states parties to the Rome Statute, the crime of genocide occurring in non-party countries remains a global concern. This article examines how the ICC can exercise its jurisdiction over individuals from non-party states through a normative juridical approach, reviewing the principles of universality, the principle of state responsibility, and the principle of non-impunity as the basis for the legitimacy of international law. This research shows that the ICC has several mechanisms to overcome the limitations of formal jurisdiction, including through referrals to the UN Security Council, territorial jurisdiction if some elements of the crime occur in the state party, personal jurisdiction over the perpetrator who is a citizen of the state party, and ad hoc approval based on the Rome Statute. Nonetheless, the implementation of ICC law enforcement challenges against non-party states faces significant obstacles, including the denial of cooperation based on state sovereignty, geopolitical bias in the Security Council, and imbalances between large and small states in international law enforcement. In this study, it is emphasised that the ICC remains relevant as a complementary instrument when the national legal system is unable or unwilling to take action against the perpetrators of genocide. Reform of jurisdictional mechanisms and increased international cooperation are key to strengthening the ICC's effectiveness in upholding global justice and preventing impunity for serious crimes.